FAKTOR KEPUASAN WISATAWAN PENGGUNA TRANSPORTASI LAUT DARI BALI KE GILI TRAWANGAN - Abrar Syah, Syukriyan; Susrami Dewi, Ni Gusti Ayu; Wikanatha Sagita, Putu Agus (Jurnal IPTA (Industri Perjalanan Wisata), 2018)
This research aims to analyze factors affecting the satisfaction of tourists in the use of marine transportation from Bali toward Gili Trawangan. The benefits of this research useful to the company in improving the services for tourists who will use the services of a crosswalk leading to Gili Trawangan.The respondents in this research totalled 190 respondents, the selection of the sample using the method of purposive sampling, the data in this study were analyzed using the analysis factors that help by statistikal program SPSS version 17.0 for windows. The results of this study are: 1) the satisfaction of tourists in the use of sea transport in general are at a level of satisfaction. 2) there are three factors that affect the satisfaction of tourists formed i.e. factors quality of maids, the cost factor & ease factors and product quality. Quality of service factor is the most dominant factor influencing the satisfaction of travellers with variable reliability as the dominant variables, and the variable availability schedule is a variable that must be improved.